Epidemiological profile of women with trichomonas vaginalis assisted in primary care - Morgana Cristina Leôncio de Lima; Lays Miranda da Silva Cabral; Sara Rodrigues Cordeiro da Silva; Aline Agnes de Souza Cipriano; Jessica Tainã Carvalho dos Santos; Angela Lessa de Andrade; Maria Sandra de Andrade (Universidade de Pernambuco, 2019)
Objective: To outline the epidemiological profile of women with trichomonas vaginalis assisted in the primary health care of the city of Recife. Methods: This is a cross-sectional and retrospective study, typified as quantitative, involving a sample of 93 medical charts, whose target population was women affected by trichomoniasis. We collected socioeconomic, demographic and clinical data. Results: The prevalence of Trichomonas vaginalis was 18.5%. The age limit was between 15 and 77 years, where the most affected age group was 20-30 years, corresponding to 26.1%. When analyzing the epidemiological profile, we found that 48.9% of women are married; where 84.8% have up to 9 years of schooling. A significant association (p-value). Conclusion: Conclusions: We can conclude that the planning of new actions to combat sexually transmitted infections will contribute in reducing the prevalence of trichomoniasis.